HEDGES, POLITENESS STRATEGIES, AND POWER: A CASE STUDY OF WOMEN COMMUNITY LEADERS IN MALANG REGENCY - Asih Zunaidah; Yanuarita Kusuma P. Sari; Riesta Devi Kumalasari (Asosiasi Pendidikan Tinggi Ilmu Komuniasi (ASPIKOM) Wilayah Riau, 2020)
Gender and power related speech patterns have been a focus of communication studies. Women and power used to be in opposite side of each other. On this ground, we were intrigued to investigate whether being a female leader has something to do with defying certain assumed ideals of women speech. This case study was conducted to women leaders engaged in a social community called Pelangi Nusantara. Concerning this study, we focused on the women leaders’ speech to examine the stereotyped-speech-pattern related to the use of hedges and politeness strategies in female speakers albeit holding a high position. A descriptive qualitative approach was employed along with the purposive technique to select the interviewees. Based on the analysis, it is revealed that despite holding a high position in the community, the female leaders mostly showed the stereotyped-speech-pattern through the use of hedges, convergence, and politeness strategies as influenced by their cultural background.